Modernization of personnel management of the public sector Case of the Urban Agency of Al Hoceima - Yazzif, Kamal; El Amrany, Fatima; Baghdad, Achraf; Ouddasser, Abderrahmane (P.A. Persona e Amministrazione, 2025)
The performance and efficiency of the public administration is linked to the level of efficiency of its human resources management. These resources are considered as the main pillar for the development of the administration and its empowerment for its insertion in the social and economic sphere and for the contribution to lifting the challenges of globalization and international competition, It is in this context that the urban agency of Al Hoceima in coordination with the services of the TGR which has designed and developed a web version of the software package Gipe/Ordinator called INDIMAJ with the aim of facilitating communication with the partners of the GIPE system and to allow interfacing with the system Wadef@ujour, in order to constitute a first step of integration of the target system. The integrated management system of the State personnel is a system allowing all the participants in the process of management, control and remuneration of the personnel of the State or other organizations to apply the same rules of management, to unify the concepts and procedures and to adopt the same standards of communication as regards exchange of information by relying on modern technologies of information. Through this paper, we will try, in a first part, to present an overview of the human resources function in the public sector. In a second part, we will proceed to a reflection on the advantages and disadvantages of computer system in the management of human resources in the public sector.